Quality, reliability, security and robustness in heterogeneous systems : 13th International Conference, QShine 2017, Dalian, China, December 16 -17, 2017, Proceedings /: 13th International Conference, QShine 2017, Dalian, China, December 16 -17, 2017, Proceedings. (2018) - Unknown
No abstract available